The Reform of the International Financial Architecture - Lastra, Rosa María. (London ; Boston : Kluwer Law International, 2001)
This work offers an incisive and comprehensive legal overview of various aspects of the reform debate, analysing the proposed parameters of the new financial architecture, the legal infrastructure in emerging economies, and the challenges that the international institutions face in the 21st century. The three main parts of the book focus on the reform of the international institutional framework, the prevention and resolution of liquidity crises, and the approaches taken by European Union institutions. The Reform of the International Financial Architecture brings together a distinguished panel of experts from practice and academia and is essential reading for academics, policy-makers, and practitioners in the financial world. This volume is one of a number of works containing the results of a global series of high-level conferences held in 1999, on the topic of `Financial Crises and the New International Financial Architecture.'
Papers presented at a conference in London in May 1999.
Includes bibliographical references (p. 337-363) and index.
rpm 08/09/16
Loans
Keywords: Banks and banking, International; Financial institutions, International; International finance; Financial crises